Sustainable biofuels : opportunities and challenges - Ray, Ramesh C. (Applied biotechnology reviews series., 2021)
Sustainable Biofuels: Opportunities and challenges, a volume in the "Applied Biotechnology Reviews" series, explores the state-of-the-art in research and applied technology for the conversion of all types of biofuels. Its chapters span a broad spectrum of knowledge, from fundamentals and technical aspects to optimization, combinations, economics, and environmental aspects. They cover various facets of research, production, and commercialization of bioethanol, biodiesel, biomethane, biohydrogen, biobutanol, and biojet fuel. This book discusses biochemical, thermochemical, and hydrothermal conversion of unconventional feedstocks, including the role of biotechnology applications to achieve efficiency and competitiveness. Through case studies, techno-economic analysis and sustainability assessment, including life cycle assessment, it goes beyond technical aspects to provides actual resources for better decision-making during the development of commercially viable technology by researchers, PhD students, and practitioners in the field of bioenergy. It is also a useful resource for those in adjacent areas, such as biotechnology, industrial microbiology, chemical engineering, environmental engineering, and sustainability science, who are working on solutions for the bioeconomy. The ability to compare different technologies and their outcome that this book provides is also beneficial for energy analysts, consultants, planners, and policy-makers. The "Applied Biotechnology Reviews" series highlights current development and research in biotechnology-related fields, combining in single-volume works the theoretical aspects and real-world applications for better decision-making